Threat of Bankruptcy and Earnings Management in Nigerian Listed Banks - Patrick Amaechi Egbunike (Acta Universitatis Danubius: Oeconomica, 2018)
The study examines the impact of bankruptcy threats on the likelihood of earnings manipulation in Nigerian listed banks. There is robust empirical evidence on the relationship between bankruptcy threat and earnings management in other countries while scanty evidence exists in Nigeria, hence this study was carried out in order to see if such results obtainable in other countries may hold in Nigeria. Using Altman Z-score and Beneish M-score, the expost-facto research design within a panel framework was employed and binary regression models were used in testing the hypothesis of the study via Eview 8.0. The study period is 2011-2015. The result reveals that bankruptcy threat has no significant impact on the likelihood of an upward earnings manipulation in Nigeria listed banks. The implication is that manipulation of earnings in Nigerian banks is spurred significantly by other factors outside the threat of bankruptcy. By this, regulators and bank managements are to place less emphasis on the bankruptcy position of banks when probing into issues of earnings manipulation because banks manipulate earnings not just because of the threat of bankruptcy, as non-potentially bankrupt firms also engage in upward earnings manipulation. Using the Altman Z-score and Beneish M-score, the study contributes to literature on the relationship between bankruptcy threat and earnings manipulation and submit that non-potentially bankrupt firms involve in upward earnings manipulation.